[123I]FP-CIT SPECT in atypical degenerative parkinsonism. (August 2012) - Isaias, Ioannis U; Marotta, Giorgio; Pezzoli, Gianni; Sabri, Osama; Hesse, Swen
One of the most widely used techniques to support the clinical diagnosis of Parkinson's disease is the SPECT scan with [ 123 I]FP-CIT. This tracer binds reversibly and visualizes the striatal presynaptic dopamine transporters. Several uncertainties remain on the value of [ 123 I]FP-CIT and SPECT in atypical degenerative parkinsonian syndromes. In this concise review, we discuss the contribution of SPECT and [ 123 I]FP-CIT in supporting the clinical diagnosis of Parkinson's disease and their role in the differential diagnosis of Parkinson's disease and atypical degenerative parkinsonism. The chemistry, pharmacodynamics and pharmacokinetics of [ 123 I]FP-CIT are also discussed.